Guidelines for Sustainable Intensification of Wheat Production in Uzbekistan - Devkota, Krishna; Amanov, Oybek; Juraev, Diyor; Dilmurodov, Sherzod; Devkota Wasti, Mina Kumari; Boysunov, Nurzod; Bakhromova, Nilufar; Abdimajidov, Jaloliddin; Meyliyev, Akmal; Nurbekov, Aziz (2024)
The guidelines and customized bundle solution ‘good agricultural practices (GAPs)’ detailed in this book aim to support Uzbek farmers in sustainably increasing wheat productivity. By promoting environmentally sound farming methods and nature-based solutions, the adoption of GAPs will help minimize the environmental impact of agricultural practices while improving food quality and ensuring livelihoods for farming communities.